Successful ACL reconstruction with a variant of the pes anserinus - Shelain Patel; Ravi K. Trehan; Gil T. Railton (Journal of Orthopaedics and Traumatology, 2009)
Abstract An anatomical variant of the pes anserinus encountered during anterior cruciate ligament reconstructive surgery which has not been previously described is discussed. During routine harvesting, the sartorius fascia was incised and the semitendinosus and gracilis tendons were identified. At the distal portion, it was noted that each tendon gave off an additional tendinous slip. The slip from the semitendinosus tendon had attached to the gracilis tendon and vice versa, thereby creating a double pes anserinus. This variant was used to construct the graft, and at 1 year review the patient had returned to full sporting activities with no complications encountered.